The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1179/174329409x409477
|View full text |Cite
|
Sign up to set email alerts
|

Erosion–corrosion behaviour of nano-Al2O3 reinforced Ni based alloying layer in acidic slurry flow

Abstract: The aim of the present study was to study the effect of nano-Al2O3 particles on erosion–corrosion behaviour of Ni based alloying layer in acidic slurry flow. The nano-Al2O3 reinforced Ni based alloying layer was prepared by double glow plasma alloying on 316L stainless steel surface, where Ni/nano-Al2O3 was firstly predeposited by brush plating. AISI 316L stainless steel and single Ni based alloying layer without Ni/nano-Al2O3 interlayer were used as reference materials. Potentiodynamic polarisation, electroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…3. 17,24 During the impact process, the kinetic energy of the erodent particle is transferred directly to the coating and materials are removed by formation of cracks. 35 The velocity of the impacting sand particles varies at different sections of volute.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3. 17,24 During the impact process, the kinetic energy of the erodent particle is transferred directly to the coating and materials are removed by formation of cracks. 35 The velocity of the impacting sand particles varies at different sections of volute.…”
Section: Resultsmentioning
confidence: 99%
“…The interactions between the processes of erosion and corrosion have only been evaluated for a limited range of parameters, though in reality erosion-corrosion occurs over a wide range of variables. 24 The exposure of substrate to the water should be least for minimising corrosion and for this porosity has to be kept close to zero. Inspection of failed components revealed that the failure process is corrosion initiated and then erosion dominant corrosion initiated layers are removed faster due to combination of factors like micro pitting, local cavitations and impulsive jet of water with sand erodents.…”
Section: Other Influencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, hardness increased significantly due to the uniformly distributed secondary hard carbides and hard complex phases. Zhuo and associates deposited a nano-Al 2 O 3 reinforced Ni-based alloying layer by plasma alloying to have better erosion resistant 316L steel [94]. They found the increased erosion resistance beyond a certain rotational speed.…”
Section: Surface Modificationsmentioning
confidence: 99%
“…Electric brush plating technology, as one of the methods of electrodeposition, has been applied widely to fabricate metallic and composite coatings in engineering 68 The coatings can be deposited on the surfaces of arbitrary size and shape.…”
Section: Introductionmentioning
confidence: 99%